Imprints of Contemporaries on Ahmad Nadeem Qasmi - Muhammad Abbas (بازیافت)
<span style="font-size: 12.0pt; line-height: 107%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: FA;">Ahmed Nadim Qasmi is a prominent personality of Urdu literature. Much has written about him. But still some hidden angels are there to be unveil. In thi article it has been analyzed that how Ahmed Nadim Qasmi was influenced by his contemporary literary figures. We have found a lot of examples that Ahmed Nadim Qasmi used to get inspiration from his close friends or literary mentores. This study will bring in light a new angle for studying Nadim’s art and thought. By using comparative analysis, examples from poetic and fictinal works of the contemporaries of Ahmad Nadeem Qasmi are brought forth to argue that Qasmi had a great ability to assimilate the tone, style and themes of other literati.